Towards the Prediction of Global Solution State Properties for Hydrogen Bonded, Self‐Associating Amphiphiles. Issue 30 (3rd May 2018) - White, Lisa J.; Tyuleva, Stilyana N.; Wilson, Ben; Shepherd, Helena J.; Ng, Kendrick K. L.; Holder, Simon J.; Clark, Ewan R.; Hiscock, Jennifer R.
Abstract: Through this extensive structure–property study we show that critical micelle concentration correlates with self‐associative hydrogen bond complex formation constant, when combined with outputs from low level, widely accessible, computational models. Herein, we bring together a series of 39 structurally related molecules related by stepwise variation of a hydrogen bond donor–acceptor amphiphilic salt. The self‐associative and corresponding global properties for this family of compounds have been studied in the gas, solid and solution states. Within the solution state, we have shown the type of self‐associated structure present to be solvent dependent. In DMSO, this class of compound show a preference for hydrogen bonded dimer formation, however moving into aqueous solutions the same compounds are found to form larger self‐associated aggregates. This observation has allowed us the unique opportunity to investigate and begin to predict self‐association events at both the molecular and extended aggregate level. Abstract : A readily accessible step‐change towards predicting the global effects of hydrogen bonded self‐assembly. Here we experimentally validate the first steps towards predicting the role of hydrogen bonding in extended aggregate formation with the use of simple, low level computational modelling methods.